PENGARUH PRODUCT QUALITY, ATTITUDE OF CUSTOMERS DAN PERCEIVED BEHAVIORAL CONTROL TERHADAP PURCHASE INTENTION PADA UMKM PRODUK KUE - Calvin Johari; Keni Keni (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, Universitas Tarumanagara, 2022)
Penelitian ini memiliki tujuan untuk menganalisa apakah variabel product quality, attitude of customers serta perceived behavioral control memiliki pengaruh terhadap variabel dependen yaitu purchase intention pada UMKM produk kue. Penelitian ini menggunakan populasi dari seluruh konsumen UMKM produk kue. Sample dari penelitian ini dikumpulkan dengan cara convenience sampling yang menghasilkan 172 responden yang dijadikan sample penelitian ini yang sesuai dengan kriteria yang diinginkan peneliti. Metode analisis data yang digunakan di penelitian ini adalah SEM (Structural Equation Model) dan uji hipotesis pada software SmartPLS. Hasil dari penelitian ini menyimpulkan bahwa variabel product quality, attitude of customers dan perceived behavioral control memiliki pengaruh yang positif dan signifikan terhadap variabel dependen purchase intention. Industry performance in the food and beverage sector is one of the leading industries and continues to experience movement resulting in creating a very tight competition. Every business is competing to win the hearts of consumers and be the best in their industry. Therefore, an analysis is needed that will produce a strategy for business in carrying out their operations. This research has the objective to analyze the variables of product quality, attitude of customers and perceived behavioral control have influence to the dependent variable which is purchase intention at Small and Medium Enterprise (SME) that provides cake. This research using the population of all customers at Small and Medium Enterprise (SME) that provides cake. The sample from this research was collected by convenience sampling and there were 172 respondents who were used as samples in this study. Respondents from this research were all consumers of Small and Medium Enterprise (SME) cake products. The data analysis method that used in this research are SEM (Structural Equation Model) and hypothesis testing on SmartPLS software. The result of this research concludes that the variables of product quality, attitude of customers